Pharmacokinetics of first-line tuberculosis drugs in Tanzanian patients - Tostmann, Alma; Mtabho, Charles M; Semvua, Hadija H; van den Boogaard, Jossy; Kibiki, Gibson S; Boeree, Martin J; Aarnoutse, Rob E (Antimicrobial agents and chemotherapy, 2013)
East Africa has a high tuberculosis (TB) incidence and mortality, yet there are very limited data on exposure to TB drugs in patients from this region. We therefore determined the pharmacokinetic characteristics of first-line TB drugs in Tanzanian patients using intensive pharmacokinetic sampling. In 20 adult TB patients, plasma concentrations were determined just before and at 1, 2, 3, 4, 6, 8, 10, and 24 h after observed drug intake with food to estimate the areas under the curve from 0 to 24 h (AUC0-24) and peak plasma concentrations (Cmax) of isoniazid, rifampin, pyrazinamide, and ethambutol. Acetylator status for isoniazid was assessed phenotypically using the isoniazid elimination half-life and the acetylisoniazid/isoniazid metabolic ratio at 3 h postdose. The geometric mean AUC0-24s were as follows: isoniazid, 11.0 h · mg/liter; rifampin, 39.9 h · mg/liter; pyrazinamide, 344 h · mg/liter; and ethambutol, 20.2 h · mg/liter. The Cmax was below the reference range for isoniazid in 10/19 patients and for rifampin in 7/20 patients. In none of the patients were the Cmaxs for pyrazinamide and ethambutol below the reference range. Elimination half-life and metabolic ratio of isoniazid gave discordant phenotyping results in only 2/19 patients. A substantial proportion of patients had an isoniazid and/or rifampin Cmax below the reference range. Intake of TB drugs with food may partly explain these low drug levels, but such a drug intake reflects common practice. The finding of low TB drug concentrations is concerning because low concentrations have been associated with worse treatment outcome in several other studies.